1963
DOI: 10.1029/jz068i016p04723
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of performance of five rain-gage installations

Abstract: The daily rain, snow, or mixed‐rain‐and‐snow catch by five different rain‐gage installations was measured near Hastings, Nebraska, during the period January 1946 through September 1961. Rain‐gage installations included were a U.S. Weather Bureau standard 8‐inch gage, a weighing‐recording gage, a standard gage on a 6‐foot post, a standard gage equipped with an Alter shield, and a standard gage equipped with a Nipher shield. The shielded gages caught slightly more precipitation (significant at 1 per cent level) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
3
8
0
Order By: Relevance
“…The results from this study agree with those reported by Allis et al (1963) where they found an undercatch of approximately 3% between shielded and unshielded gauges. Hanson (1989) reported an undercatch of approximately 8% for the BELUNSHLD system.…”
Section: Rainsupporting
confidence: 93%
See 4 more Smart Citations
“…The results from this study agree with those reported by Allis et al (1963) where they found an undercatch of approximately 3% between shielded and unshielded gauges. Hanson (1989) reported an undercatch of approximately 8% for the BELUNSHLD system.…”
Section: Rainsupporting
confidence: 93%
“…The DFIR, TRET, BELUNSHLD, and BELSHLD all caught significantly lesser amounts of rain than the WYO as wind speeds increased. These results agree with earlier studies by Allis et al (1963), Hanson (1989), andNeff (1977), which showed that gauge shielding is required for the most accurate measurement of rain.…”
Section: Rainsupporting
confidence: 93%
See 3 more Smart Citations